Causes of concomitant strabismus surgery delay in teenagers and adults. (3rd July 2021) - Paduca, Ala; Arnaut, Oleg; Lundmark, Per Olof; Bruenech, Jan Richard
ABSTRACT: To reveal the reasons for strabismus surgery delay and motivations for seeking surgical treatment in adulthood. Prospective survey among 91 adult patients, suffering from concomitant strabismus acquired in the childhood that underwent delayed strabismus surgery. The mean age of participants was 24 years (from 16 to 58 years); 48 females (52.7%), and 43 males (47.3%). Strabismus surgery has been delayed for about 20 years in adult patients who could potentially benefit of it in childhood. The most common reasons for strabismus surgery delay, reported by patients, included the following: lack of awareness about surgery (37.4%); surgery was recommended but declined by patients' parents/guardians in their childhood (6.6%); fear of surgery (17.6%); eye specialists affirmation that surgery would not lead to strabismus improvement (27.5%); previous poor surgical experience (6.6%); and non-affordability (4.4%). The main motivations for seeking strabismus surgery in adulthood among our patients were the following: appearance improvement (38.5%), strengthening of self-confidence (30.8%), better social relationship (16.5%), better job opportunities (7.7%), and advice from family and friends (6.6%). About 80% of strabismus surgery delays in teenagers and adults were caused by lack of awareness regarding strabismus surgery and even the misconception among primary health-care practitioners and some eye doctors who considered that surgery would not lead to strabismus correction. The main reasons for seeking strabismus surgery in adulthood were: esthetical ones, self-confidence strengthening, and building better social relationship. All factors mentioned below confirmed the negative impact of oculomotor disorders on patient's psychological condition. The focus on patient's individual concerns and needs was especially important for recovery and well-being of adult patients with strabismus and formed a central feature of patient centered medical approach.